Chlorophyll fluorescence parameters to assess utilization of excitation energy in photosystem II independently of changes in leaf absorption - Semer, J; Navrátil, M; Špunda, V; Štroch, M (Journal of photochemistry and photobiology. B, Biology, 2019)
Measurement of Pulse-Amplitude-Modulated (PAM) chlorophyll a fluorescence is widely used method for obtaining information on the functional state of photosystem II (PSII). Recently, it has been shown that some of long-established fluorescence parameters must be interpreted with caution, when the light-induced chloroplast movements occur. In our work we have analyzed the effect of chloroplast movements on these parameters. We have derived new parameters that are independent of the change in PSII absorption occurring during measurement. To verify whether there is a need for new parameters or the difference between the parameters commonly used and the newly derived ones is insignificant, we conducted an experiment with Arabidopsis thaliana wild type plants and its phot1 phot2 mutant defective in chloroplast movement. Plants were exposed to light of different qualities (450, 470, 550 or 660 nm) and quantities (100, 400 or 1200 μmol m-2 s-1) for up to 40 min. Since the blue light-induced chloroplast avoidance reaction is a photoprotective mechanism, we expected that phot1 phot2 mutant will compensate the lack of this mechanism by increasing non-photochemical quenching. However, using the light at both 450 and 470 nm, the calculation of commonly used parameter, ΦNPQ (quantum yield of regulated light-induced thermal energy dissipation in PSII) based on Hendrickson et al. [L. Hendrickson, R.T. Furbank, W.S. Chow, Photosynth. Res. 82 (2004) 73-81] showed the opposite. On the other hand, the results obtained using our newly proposed formulae to determine quantum yield of PSII thermal energy dissipation were in line with our assumption. Thus, the experimental data showed that some formulae of fluorescence parameters are dependent on the change in PSII absorption and need to be interpreted carefully. On the contrary, the formulae introduced by us can remove the effect of changes in PSII absorption that occur during measurement, without additional measurements, and give the real estimate of light-induced non-photochemical quenching.
Keywords: proteiny huseníčku; listy rostlin; Chlorophyll fluorescence; Arabidopsis thaliana; Arabidopsis; chlorofyl a; chloroplasty; Thermodynamics; teoretické modely; Arabidopsis Proteins; kvantová teorie; Chloroplasts; Photoprotection; Chlorophyll A; světlo; termodynamika; Models, Theoretical; mutageneze; Chloroplast movement; Photosystem II quantum yields; Plant Leaves; Photosystem II Protein Complex; Quantum Theory; Mutagenesis; Light; fotosystém II (proteinový komplex)